Love Letters to My Child in These Hate-Filled Times - Vasudevan, Pavithra (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
In a series of three letters, Pavithra describes to their unborn child what it’s like to be pregnant. The first conveys the terror of carrying a new being into a violently homophobic and racist world. The second and third letters recall the desire and beauty that the unborn child sparks in them. In the fourth letter, Pavithra writes to Noor Momo, now six years old, reflecting on the realities of parenting amidst ongoing violence and the uncertainties of the COVID-19 pandemic. In this final letter, Pavithra invokes Noor’s aunts: her sister Raksha, and her dear friends Kriti, Batool, Mabel, and Marie. The words Chitthi, Masi, Khala and Chyama refer to “mother’s sister” in Tamil, Hindi, Urdu, and Nepali, respectively.